Upaya Mewujudkan Keluarga Sakinah pada Keluarga Petani Desa Pakondang Rubaru Sumenep - Ummi Kulsum; Moh. Zainol Kamal (Bulletin of Community Engagement, 2021)
The purpose of this assistance is the efforts of the Pakondang Village Farmer Family in Realizing the Sakinah Family, the Farmer Family's Efforts to Realize the Sakinah Family in the Perspective of Islamic Law. The type of research is qualitative. The results of this study show that each partner must understand each other, advise, understand, and not blame each other and provide mutual support to the couple in order to create a sakinah household, and obey religion as confirmed in QS. Ar-Rum: verse 30. With this it can be concluded that there is harmony between the sakinah family in the perspective of Islamic law and the efforts made by the Pakondang Village Farmer family. As the results of the author's interview with the Pakondang Village Farmer's family about the sakinah family, most of the respondents explained that the sakinah family is the achievement of physical and mental happiness, prosperity, peace, peace, full of affection between family members, living in harmony and happily fulfilling all the necessities of life and existence. good communication between families, and maintain devotion to God. Sakinah family is meant here is a family that is able to maintain peace, and has love and affection. The elements of love and affection must exist to complement each other so that the couple can make each other happy. Keywords: Realizing the Sakinah Family, Sakinah Family in Islamic Law, Sakinah Family